2016
DOI: 10.22159/ijpps.2016v8i11.13000
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices (Kap) on Good Manufacturing Practices (Gmp) Among Food Handlers in Terengganu Hospitals

Abstract: Objective: This study was conducted to study the level of knowledge, attitudes and practices (KAP) on good manufacturing practices (GMP) among food handlers in Terengganu hospitals. Methods:A cross-sectional study was done with four hospitals involved. Then, sampling method used was purposive convenience sampling. The data had been collected using a method of a questionnaire and being analyzed by using Statistical Package for Social Science (SPSS) 20.0 version. Results:The findings from this study indicate tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…This result is consistent with a study in Beirut, Lebanon by Bou-Mitri et al [14], in which it was noticed that an average level of KAP of 59.2%, 83.7% and 83.2%, respectively. However, the findings of a study in Malaysia by Rohin et al [15] concerning knowledge score is contrary with our results, which found a good knowledge level of 83%; and approximately in accordance with our findings regarding attitude and practice score of 87.2% and 90.7%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…This result is consistent with a study in Beirut, Lebanon by Bou-Mitri et al [14], in which it was noticed that an average level of KAP of 59.2%, 83.7% and 83.2%, respectively. However, the findings of a study in Malaysia by Rohin et al [15] concerning knowledge score is contrary with our results, which found a good knowledge level of 83%; and approximately in accordance with our findings regarding attitude and practice score of 87.2% and 90.7%, respectively.…”
Section: Discussionsupporting
confidence: 74%
“…Bou-Mitri et al [31] reported higher attitude and overall KAP scores for food handlers of Lebanese government hospitals with long working experience. Parallelly, Sharif et al [50] found higher overall KAP scores for females and handlers with higher education levels and Norhaslinda et al [51] for older food handlers.…”
Section: Discussionmentioning
confidence: 98%
“…In the current study, there were more female participants in the control group than the intervention group. Previous KAP studies reported that females tend to have higher knowledge, attitude, and practice in food poisoning prevention than males [77,78]. Similarly, Malhotra et al [79] conducted a study to evaluate the impact of a health education intervention on knowledge and attitude towards food, personal hygiene, and self-reported handwashing practices and found that female respondents exhibited higher knowledge about food hygiene practices since they were routinely involved in food preparation.…”
Section: Discussionmentioning
confidence: 99%